ON TUNING THE DYNAMIC LOAD BALANCING FEM FRAMEWORK - Michal Bošanský; Bořek Patzák (Acta Polytechnica CTU Proceedings)
Developments in computer hardware are currently bringing new opportunities for numerical modelling. The current trend in technology is parallel processing making use of multiple processing units simultaneously to solve a given problem. This paper deals with exploring the parallel dynamic load balancing framework implemented in the finite element software. This framework is based on a domain decomposition paradigm for distributed memory model. The paper describes the improved technique to determine the actual processor weights related to performance of individual processing units. The load recovery consisting in mesh (re)partitioning is based on actual processor weights. The (re)partitioning process has to be performed during the simulation and whenever the load imbalance is significant. The performance of the proposed technique is tested on the benchmark problem and discussed.